VAKSIN COVID 19 DI INDONESIA : ANALISIS BERITA HOAX - ROCHANI NANI RAHAYU,; SENSUSIYATI, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
One of the Indonesian government’s efforts to fight Covid 19 id to vaccinate all Indonesians. Hohever, this effort encountered problems with the emergence of hoax news in various media. Therefore, this ppaper was written with the aim of finding out hoax news about the Covid 19 vaccine regarding 1) Hoax bout the composition of the Covid 19 vaccine; 2) Hoax about the impact of the Covid 19 vaccine; 3) Hoax about rejecting the Covid 19 vaccine. The research used the rivew method with the souece of the data analyzed were data traced from the Google search engine. Search keywords werw used, namely Civid 19vaccine news and hoaxes. The serch period is limited to three months, from November 2020 to January 2021 from online mass media. Based on the search results, there were 58 search results about Covid 19 vaccine news and hoaxes. Furthermore, the data were compiled, analyzed, reviewed according to research objectives and found as many as 13 relevant news headlines. The results showed hoax news about the Covid 19 vaccine related to its composition, that the Covid 19 vaccine contained dangerous ingredients including borax, formalin, vero cells, and some evensaid the vaccine was made from a male fetus. The hoaxes about side effects include death, infertility, enlarging male genitalia, and modifiying human DNA. Hoax on vaccine refusel is the unavailability of the Indonesian Doctor Association as an organization of doctors not willing to be vaccinated for the first time. It was concluded that was hoax news about the Covid 19 vaccine circulating in Indonesia from November 2020 to January 2021.